Corporate Social Responsibility of Islamic and Conventional Banks: Evidence in Bahrain - Abdulla Hamzah Al-Hadrami; Sutan Emir Hidayat (Faculty of Economic and Business, 2019)
Several researchers found a positive relationship between the company's performance and corporate social responsibility (CSR) activities. The current study aims to explore the clients' awareness and perception of CSR in Islamic and conventional banks across Bahrain. The study surveyed 305 clients that 175 from the Islamic banks, and 130 from the conventional banks. The results indicated that the clients of Islamic banks are more aware of their banks CSR activities than the clients of conventional banks. The result shows that Islamic banks clients have a more positive perception of their banks' CSR than those of the conventional banks. Additionally, the results indicated that there are statistically significant differences in the clients' awareness and perception of banks' CSR activities when the client's group according to age, income, education, and bank type.JEL Classification: G21, M14